2008
DOI: 10.1136/bjo.2008.138172
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of the lateral geniculate nucleus in human glaucoma detected by magnetic resonance imaging

Abstract: Aim: To determine in vivo whether the lateral geniculate nucleus (LGN) undergoes atrophy in patients with glaucoma and vision loss compared with normal subjects. Methods: Following institutional St Michael's Hospital Research Ethics Board approval, a prospective and masked neuroimaging study was conducted on glaucoma patients with visual-field defects affecting both eyes (n = 10) and age-matched controls (n = 8). Following informed consent, all subjects underwent 1.5-Tesla MRI. Coronal proton density magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
130
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 19 publications
(24 reference statements)
12
130
0
2
Order By: Relevance
“…7 The present study elaborates on this initial observation in a much larger patient cohort and correlates the degree of LGN atrophy to the clinical stage of glaucoma present. This article is the first, to the knowledge of the authors, to show this association, which may have important applications for noninvasive assessment of glaucoma severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The present study elaborates on this initial observation in a much larger patient cohort and correlates the degree of LGN atrophy to the clinical stage of glaucoma present. This article is the first, to the knowledge of the authors, to show this association, which may have important applications for noninvasive assessment of glaucoma severity.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Gupta et al 6 reported the first clinicopathologic case of human glaucoma, demonstrating degenerative changes in the brain involving the intracranial optic nerves, LGN, and visual cortex in 2006. Three years later in vivo MR imaging evidence of LGN degeneration in human glaucoma was found, which was consistent with ex vivo primate and human neuropathologic studies.…”
mentioning
confidence: 99%
“…23 A postmortem study of human glaucoma with bilateral visual-field loss, by using histomorphometry and ex vivo MR imaging, demonstrated reduced LGN and neuron size. 5 Gupta et al, 24 after obtaining LGN height measurements in vivo by 1.5T MR imaging, reported LGN atrophy in patients with glaucoma with symmetric bilateral visual-field defects. In contrast, in the present study, more pronounced atrophy was found on the left side, and this is probably related to the more pronounced atrophy of the right nasal and left temporal retinal fibers found with OCT and may be due to the small sample, because POAG is often a bilateral condition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence that developmental visual disorders such as amblyopia (Mendola et al, 2005) and albinism (von dem Hagen et al, 2005) affect the structure of the human occipital cortex. A reduced size of the lateral geniculate nuclei has been reported in patients with glaucoma (Gupta et al 2009) and reduction in grey matter density was found in the retinal lesion projection zones of the visual cortex in patient with age-related macular degeneration (Boucard et al 2009). As the proportion of individuals over the age of 65 increases, institutions serving the housing needs of people with degenerative diseases are becoming more numerous.…”
Section: Conclusion and Future Researchmentioning
confidence: 95%